Democratic Principles and Nepal’s Electoral System (Pragyaratna प्रज्ञारत्न, 2025)
Elections are the basic foundation of democracy. Representatives of the people are elected in elections. Ancient Greece was a small city-state. There were very strict provisions for political participation. At that time, citizens continued to practice direct democracy with a small number. Although citizens were not directly involved in governance, they adopted the process of electing representatives through their representatives. Since elections are the basis of democracy, it is considered necessary in the process of running a state. In fact, elections are also a regular process of understanding the opinions or wishes of the general public. Because in modern political systems, elections are a process of understanding the opinions of the people. Democracy is found to be conducted in two ways: direct and indirect. In direct democracy, the people themselves directly participate and run their state system. Forming a government, formulating rules, implementing them, and administering justice are the concepts of direct democracy. Elections are the main means of political recruitment. This is a powerful means of legitimizing power. Currently, indirect elections and systems are being implemented in practice. Nowadays, due to the large states and large populations, all the people cannot gather at once and make any decisions. Therefore, it is customary for the people to elect their representatives to run the state or government. After such representatives are elected by the general public, they run the government according to the democratic system.The system of running the state through such representatives of the people is called indirect democracy or representative democracy. In fact, the modern system of popular representation is considered a great invention and achievement of democracy. The modern representative system elects a democratic government that exists in the name of the entire people, but is formed by the majority of the people. Countries around the world have adopted different electoral systems. There are four types of electoral systems in operation, including the first-past-the-post system, the proportional electoral system, and the mixed electoral system. In addition, there are 12 electoral systems. Thus, since one of the beautiful aspects of democracy is elections, its importance is increasing day by day. Various electoral systems have played an important role in the establishment of peace and security, the development of political freedom, and the establishment of the rule of law. Since elections are the standard and expression of democracy, the people exercise their sovereign rights through elections. Although elections are not the solution to regional, ethnic, communal, religious, and other disputes, they present alternatives in the process of building a democratic system.